10Be exposure age constraints on the Late Weichselian ice‐sheet geometry and dynamics in inter‐ice‐stream areas, western Svalbard. (10th October 2012) - Landvik, Jon Y.; Brook, Edward J.; Gualtieri, Lyn; Linge, Henriette; Raisbeck, Grant; Salvigsen, Otto; Yiou, Françoise
Abstract : The Late Weichselian ice sheet of western Svalbard was characterized by ice streams and inter‐ice‐stream areas. To reconstruct its geometry and dynamics we investigated the glacial geology of two areas on the island of Prins Karls Forland and the Mitrahalvøya peninsula. Cosmogenic 10 Be surface exposure dating of glacial erratics and bedrock was used to constrain past ice thickness, providing minimum estimates in both areas. Contrary to previous studies, we found that Prins Karls Forland experienced a westward ice flux from Spitsbergen. Ice thickness reached >470 m a.s.l., and warm‐based conditions occurred periodically. Local deglaciation took place between 16 and 13 ka. At Mitrahalvøya, glacier ice draining the Krossfjorden basin reached >300 m a.s.l., and local deglaciation occurred at c . 13 ka. We propose the following succession of events for the last deglaciation. After the maximum glacier extent, ice streams in the cross‐shelf troughs and fjords retreated, tributary ice streams formed in Forlandsundet and Krossfjorden, and, finally, local ice caps were isolated over both Prins Karls Forland and Mitrahalvøya and their adjacent shelves.